Evaluating Suppliers’ Efficiency using Conjoint Analysis - Iqbal, Z.; Ali, H. M.K.; Wasim, A.; Hussain, S.; Jahanzaib, M. (The Nucleus, 2016)
One of the main challenges for leading manufacturing industries to retain their competitiveness is selection of appropriate suppliers. In developing countries like Pakistan, industries need reinforcement of the supplier selection decisions using scientific techniques. This study utilizes conjoint analysis (CA), a mathematical and statistical modeling based multi-criteria decision making (MCDM) methodology, for evaluation of supplier efficiency in a real world manufacturing organization. Six attributes are extracted from respective literature with the help of expert opinions. The developed mathematical models are solved in respective CA software by using actual data. Results reveal that product performance is the most important attribute in supplier evaluation for the concerned industry followed by costs, quality, financial stability, delivery time and technical ability respectively. The findings are beneficial for both the selected manufacturing industry and the market suppliers.